APPLICATION OF THE DIGITAL FORMAT IN THE EDUCATIONAL PRACTICE OF THE UNIVERSITY - Pashchenko A.Yu. ,; Jalbe M.G.,; Gladysheva A.A. ,; Gladyshev A.A. , (Theory and Practice of Physical Culture, 2023)
Objective of the study was to assess the degree of students' awareness of the emergence of a new format of physical culture and sports - digital sports. The study of interest in the use of the digital format in the classroom at the university. Methods and structure of the study. The study was conducted in the period November 2022 - March 2023 at Irkutsk State Transport University (ISTU) and Nizhnevartovsk State University (NVSU). The study used a specially designed questionnaire. 127 people took part in the survey. Of these, 50 girls and 77 boys of 1-3 courses of various areas of training. 10 training groups of boys and girls participated in the pilot training in the phygital format. Results and conclusions. The development of digital sports solves the current problem by combining the achievements of young people in the field of computer games and physical activity, thereby contributing to an increase in the level of physical activity, the development of new skills and the improvement of existing ones against the background of increasing physical fitness. Digital transformation, on the part of the pedagogical community, caused sharp rejection by its ill-conceivedness, hasty decisions and, most importantly, the complete disregard for hygienic, psychological and medical recommendations related to the peculiarities of the age development of students when using digital devices. The new format for integrating computer gaming technologies and active motor activity arouses increased interest among students and can positively influence the increase in young people's motivation to perform physical exercises and increase the level of physical activity of the younger generation.